The future of GIS on the WEB - Daman, Daut (2000)
Web-GIS allows the wealth ofspatial data to be access and shared among Internet users all over the world. Web-GIS capability to give the basic functions of map view such as zoom, pan, query and analysis allows the systems to incorporate various types of information. In spite of great progress made, in the evolvement of Web-GIS, there are still more issues to be resolved. This paper will present two ofsuch issues, which are 3D-WebGIS and transmitting spatial data on web. Future issues such as public participation, virtual 3D-Web GIS and public participation GIS is also highlighted.